Still dizzy after all these years: a 90-year-old woman with a 54-year history of dizziness. (15th September 2011) - Smirnova, Alina; Bell, Stephanie H; Tracy, C Shawn; Upshur, Ross EG
Abstract : This report presents the case of a 90-year-old female with a 54-year history of dizziness, which has been exhaustively investigated. Over the years, the patient made 59 visits to her family doctor and 18 visits to various specialists, as well as emergency department visits and hospitalisations. In detailing the exhaustive investigations and referrals that the patient has undergone over many years (with inconclusive results), this case illustrates the myriad challenges in diagnosing and treating chronic dizziness in the older. The authors suggest that, in complex cases characterised by multimorbidity and polypharmacy, a function-oriented approach is indicated. In place of the conventional 'diagnose and treat' model, a functional approach to ongoing care emphasises the symptom management, improvement of function and quality of life. To optimise patient outcomes, an interprofessional team approach is preferred.